OPTIMASI METODE EKSTRAKSI KUERSETIN DARI DAUN KELOR (Moringa oleifera L.) - Laksmiani, N. P. L.; Widiantara, I W. A.; Adnyani, K. D.; Pawarrangan, A. B. S. (Jurnal Kimia (Journal of Chemistry); Vol.14 No.1 Januari 2020, 2020)
Moringa plants is very abundant in Indonesia. Moringa leaves are a source of polyphenol compounds, namely flavonoids. One of the main flavonoids found in Moringa leaves is quercetin. To be able to increase the concentration of quercetin from moringa plants, extraction is necessary. This study aims to determine the most optimal extraction method in extracting quercetin from Moringa leaves. Optimization of quersein extraction methods from Moringa leaves was carried out using maceration, soxhletation, and reflux methods. The solvent used was methanol acidified with 1,2 N HCl. Determination of the concentration of quercetin in the extract used a validated TLC-densitometry method. The highest rendement obtained from the maceration extraction method was 24.08 % w/w. Extraction by reflux and sochletation methods yielded rendement of 23.44 % w/w and 10.12 % w/w respectively. Qualitative analysis of quercetin in the extract was carried out by comparing its Rf value with the standard quercetin which is 0,4. The quercetin level of the extract from maceration extraction was the highest, which was 24.45 % w/w. Extraction using the soxhletation method obtained quercetin as much as 20.95 % w/w.   Keywords : quercetin, Moringa oleifera leaves, extraction method, optimization